2020
DOI: 10.1186/s12893-020-00800-0
|View full text |Cite
|
Sign up to set email alerts
|

Single-port laparoscopic percutaneous extraperitoneal closure for inguinal hernias repair in girls: using an epidural needle assisted by a towel forceps

Abstract: Background: The concept of single-port laparoscopic percutaneous extraperitoneal closure for the treatment of inguinal hernias repair in children has been practising recent years. The applicable instruments and skills are still evolving. In this study, we used an epidural needle assisted by a towel forceps to practise this minimal invasive method for inguinal hernias repair in girls. Its safety and effectiveness were studied. Methods: From July 2008 to January 2020, thirty-five girls diagnosed of indirect ingu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…The majority of study subjects in open herniotomy group were in age group of 1 to 5 years (38.46%) while in laparoscopic hernia repair group majority of the study subjects belonged to the age group of 1 to 5 and 6 to 10 years (46.15% each). These findings are correlated with the previous studies [8,9] . Regarding the sex prevalence, males are more commonly affected.…”
Section: Discussionsupporting
confidence: 93%
“…The majority of study subjects in open herniotomy group were in age group of 1 to 5 years (38.46%) while in laparoscopic hernia repair group majority of the study subjects belonged to the age group of 1 to 5 and 6 to 10 years (46.15% each). These findings are correlated with the previous studies [8,9] . Regarding the sex prevalence, males are more commonly affected.…”
Section: Discussionsupporting
confidence: 93%
“…However, laparoscopic hernia repair (LHR) has the advantages of having a concealed scar, being minimally invasive, and having the ability to detect the contralateral PPV. Many authors think that LHR may gradually replace OHR and become the main surgical method for PIH [ 5 , 6 ]. At the same time, we also noticed that some scholars still have disputes about the operation time and the recurrence rate of hernia after LHR [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…A total of 16 studies compared the incidence of metachronous hernia between the LHRE and OHR groups, and 15 of them with a total of 14,416 patients (5207 patients in the LHRE group and 9209 patients in the OHR group) with the diagnosis of unilateral inguinal hernia who received operation were assessed [21,[23][24][25][26][27]29,32,33,36,37,[40][41][42][43]. The pooled result indicated that LHRE resulted in a considerably lower incidence of metachronous hernia compared with OHR (RR: 0.11, 95% CI: 0.07 to 0.17; p < 0.00001; I 2 = 4%; Figure 2).…”
Section: Metachronous Herniamentioning
confidence: 99%
“…A total of 26 studies compared the incidence of ipsilateral recurrence hernia between the LHRE and OHR groups, and the data of 25 of them covered a total of 24,430 patients (12,626 patients in the LHRE group and 11,777 patients in the OHR group) were assessed [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][39][40][41][42][43]. The incidence of ipsilateral recurrence hernia did not differ between the LHRE and OHR groups (RR: 0.97, 95% CI: 0.59 to 1.60; p = 0.91; I 2 = 44%; Figure 3).…”
Section: Ipsilateral Recurrence Herniamentioning
confidence: 99%